Creativity and positive psychology in psychotherapy - Holm-Hadulla, Rainer M. (International review of psychiatry, 2020)
Creativity is the ability to produce something novel and useful that is a valuable contribution to a specific domain. It is a significant common factor in most forms of psychotherapy. Accordingly, it is essential to investigate its role both in psychotherapy in general and in specific approaches like relational, cognitive-behavioural, psychodynamic, systemic, and existential psychotherapy. Positive psychology in particular has pointed up the usefulness of creativity in psychotherapy. Here we draw upon a case example to show how the creative discovery of novel and useful solutions takes place in different dimensions: relational, behavioural, psychodynamic, systemic and existential. The case description demonstrates how principles of positive psychology are useful in many realms of psychotherapy. We propose an integrated model of psychotherapy that brings together different psychotherapeutic methods and is based on interdisciplinary creativity research. The integration of neuroscientific, psychological and cultural findings produced by creativity research can be expected to lead to a deeper understanding of psychotherapeutic, positive-psychological, and creative processes.